1991
DOI: 10.1111/j.1559-1816.1991.tb00500.x
|View full text |Cite
|
Sign up to set email alerts
|

Ambiguity and Guilt Determinations: A Modern Racism Perspective1

Abstract: Studies documenting the existence of prejudice in simulated juror ratings of guilt may not be directly generalizable to legal applications due to a failure to include jury instructions. Jury instructions specifying the conditions required to find a defendant guilty may serve to dissipate juror's overt prejudices. In order to investigate this hypothesis, participants read a transcript of a trial in which the race of the victim and the defendant were varied. In addition, half the participants were given jury ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
75
1

Year Published

1995
1995
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(79 citation statements)
references
References 29 publications
(7 reference statements)
3
75
1
Order By: Relevance
“…Support for aversive racism has been found in the context of affirmative action (Dovidio & Gaertner, 1996), workplace hiring (Dovidio & Gaertner, 2000), and legal decision-making (Dovidio, Smith, Donnella, & Gaertner, 1997). In addition, studies demonstrating that racial disparity in sentencing in sexual assault cases is strongest when no jury instructions (explaining the charge, burden of proof, and reasonable doubt) are present (Hill & Pfeifer, 1992;Mitchell, Haw, Pfeifer, & Meissner, 2005;Pfeifer & Ogloff, 1991, 2003 or when evidence in the case is weak (Ugwuegbu, 1979) lend support to aversive racism theory. Aversive racism also explains why defendant race may not affect participant verdict decision, which is a more guided decision, while still affecting the more flexible decision of sentence length recommendations (Klein & Creech, 1982;Mitchell et al, 2005;Pfeifer & Ogloff, 2003).…”
Section: Aversive Racismmentioning
confidence: 99%
“…Support for aversive racism has been found in the context of affirmative action (Dovidio & Gaertner, 1996), workplace hiring (Dovidio & Gaertner, 2000), and legal decision-making (Dovidio, Smith, Donnella, & Gaertner, 1997). In addition, studies demonstrating that racial disparity in sentencing in sexual assault cases is strongest when no jury instructions (explaining the charge, burden of proof, and reasonable doubt) are present (Hill & Pfeifer, 1992;Mitchell, Haw, Pfeifer, & Meissner, 2005;Pfeifer & Ogloff, 1991, 2003 or when evidence in the case is weak (Ugwuegbu, 1979) lend support to aversive racism theory. Aversive racism also explains why defendant race may not affect participant verdict decision, which is a more guided decision, while still affecting the more flexible decision of sentence length recommendations (Klein & Creech, 1982;Mitchell et al, 2005;Pfeifer & Ogloff, 2003).…”
Section: Aversive Racismmentioning
confidence: 99%
“…Most investigators con-clude that race plays a role in juror verdicts and sentencing 1 but some have found jurors to be biased against defendants of a different race (e.g., Klein & Creech, 1982;Sweeney & Haney, 1992), whereas others have found bias against defendants of the same race (McGowen & King, 1982). Some researchers have concluded that racial effects can be erased by judicial instruction (Pfeifer & Ogloff, 1991), by deliberation (Bernard, 1979), or by the absence of inadmissible evidence (Johnson, Whitestone, Jackson, & Gatto, 1995). Still other studies and meta-analyses find no evidence of racial bias (Mazzella & Feingold, 1994;McGuire & Bermant, 1977).…”
Section: Jurydecisionmakingisacomplexsetofpsychologicalmentioning
confidence: 99%
“…There is always the nagging possibility that the variables manipulated in mockjury studies, such as this one, do not operate similarly in real juries (Baumeister & Darley, 1982;Bernard, 1979;Davis, 1989;Gerbasi et al, 1977;Pfeifer & Ogloff, 1991;Weiten & Diamond, 1979). Attempts to deal with that issue have involved the use of more heterogeneous samples of jury-eligible adults, more realistic trial simulations, and the incorporation of a deliberation phase in study designs.…”
Section: Landwehr Et Al 669mentioning
confidence: 99%